The impact of COVID-19 on addiction treatment in New Zealand. (April 2022) - Rodda, Simone N.; Park, Jennifer J.; Wilkinson-Meyers, Laura; King, Daniel L.
Highlights: COVID-19 has impacted on the configuration of addiction treatment in New Zealand. Increased internet gambling, gaming, pornography, and social media presentations. Appointments during lockdown periods were frequent and shorter in duration. Distance based delivery benefits many clients but remains a barrier for some clients. Access could be improved by providing internet and equipment for video conferencing. Abstract: COVID-19 public health measures, including lockdowns, have disrupted psychological service delivery for substance use and behavioural addictions. This study aimed to examine how addictions treatment had been affected by COVID-19 related factors from the perspective of addiction and mental health service providers. Participants (n = 93) were experienced service managers and clinicians in New Zealand who completed an online survey. Clinicians reported increased presentations for problems related to internet gambling (n = 57, 61%), gaming (n = 53, 57%), social media use (n = 52, 56%), and pornography (n = 28, 30%). A qualitative analysis of responses generated six themes. Themes included service management and increased administrative burden, and service delivery reconfiguration. Access improved for some clients because of convenience and reduced structural barriers. However, online service delivery was problematic for those with unstable or no internet access and devices that could not support video conferencing and/or lack of safe, confidential or private spaces at home. Increased client complexity and restricted in-person care prompted changes to focus, and content of clinical interventions, and some respondents offered more frequent but shorter appointments. Clinicians who provided services by phone or email, rather than video conferencing, reported treatment was less effective, with reduced rapport and engagement a contributing factor. The New Zealand addictions sector has responded to COVID-19 by increasing treatment access through distance-based options. Maintaining multifaceted models of care that are agile to rapidly changing environments presents unique challenges but is critical to addressing the needs of people impacted by addiction.